Coordinated Resolved Motion Control of Dual-Arm Manipulators with Closed Chain. (3rd May 2016) - Liu, Tianliang; Lei, Yan; Han, Liang; Xu, Wenfu; Zou, Huaiwu
When applied to some tasks, such as payload handling, assembling, repairing and so on, the two arms of a humanoid robot will form a closed kinematic chain. It makes the motion planning and control for dual-arm coordination very complex and difficult. In this paper, we present three types of resolved motion control methods for a humanoid robot during coordinated manipulation. They are, respectively, position-level, velocity-level and acceleration-level resolved motion control methods. The desired pose, velocity and acceleration of each end-effector are then resolved according to the desired motion of the payload and the constraints on the closed-chain system without consideration of the internal force. Corresponding to the three cases above, the joint variables of each arm are then calculated using the inverse kinematic equations, at position-level, velocity-level or acceleration-level. Finally, a dynamic modelling and simulation platform is established based on ADAMS and Matlab software. The proposed methods are verified by typical cases. The simulation results show that the proposed control strategy can realize the dual-arm coordinated operation and the internal force of the closed chain during the operation is controlled in a reasonable range at the same time.